2018
DOI: 10.1089/dna.2017.3936
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-133a-5p Inhibits the Expression of Osteoblast Differentiation-Associated Markers by Targeting the 3′ UTR ofRUNX2

Abstract: Recent studies have recognized the involvement of microRNAs (miRNAs) in the development of osteoporosis, which regulate the balance between osteogenesis and osteoclasis. In this study, we investigated the regulation by miRNA-133a-5p on the osteoblast differentiation-associated markers in the mouse osteoblast-like MC3T3-E1 cells by RUNX2. First, we manipulated the miRNA-133a level in the MC3T3-E1 cells with 20 or 40 nM miR-133a-5p mimics, miR-133a-5p inhibitor, or scramble miRNA. Then, we quantified with real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…As shown in other human studies, miR‐133a could promote osteoclast differentiation, and its level was correlated with low BMD in postmenopausal women . It was also shown that miR‐133a could hamper bone formation by targeting RUNX2 . MiR‐33, on the other hand, was involved in mechano‐induced osteoblast differentiation, but its association with BMD has yet to be reported.…”
Section: Mirnas In Antiosteoporosis Treatmentmentioning
confidence: 77%
“…As shown in other human studies, miR‐133a could promote osteoclast differentiation, and its level was correlated with low BMD in postmenopausal women . It was also shown that miR‐133a could hamper bone formation by targeting RUNX2 . MiR‐33, on the other hand, was involved in mechano‐induced osteoblast differentiation, but its association with BMD has yet to be reported.…”
Section: Mirnas In Antiosteoporosis Treatmentmentioning
confidence: 77%
“…Thus, miR-140-3p regulated osteoblast differentiation by acting as a regulatory factor between Wnt3a and TGFβ3 signaling pathways [92]. According to the study, miR-133a-5p overexpression was shown to significantly lower the expression of osteoblast differentiation markers as well as ECM mineralization in MC3T3-E1 cells by targeting 3 UTR of Runx2 and reduce Runx2 expression at both mRNA and protein levels [93]. The expression of miR-92a-1-5p was decreased during MC3T3-E1 osteogenic differentiation, and overexpression could target β-catenin, a positive regulator of osteogenic differentiation, thereby inhibiting osteogenesis [94].…”
Section: Mirnas Involved In Osteoblast Regulationmentioning
confidence: 97%
“…However, miR-375 suppresses osteogenic differentiation by directly targeting Runx2 and, in this process, it reduces the activity levels of key osteoblast markers, including osteocalcin, ALP, and collagen type I α1 (COL1A1) [32]. miRNA-133a-5p inhibits the expression of Runx2, at both mRNA and protein levels by targeting the 3′-UTR of Runx2 [33]. As an endogenous attenuator of Smad1, miR-100 was shown to inhibit BMP-induced osteoblast differentiation [34].…”
Section: Mirna-mediated Mechanismsmentioning
confidence: 99%